KOMUNIKASI KELOMPOK PADA KOMUNITAS VESPA BROTHERHOOD SCOOTERIS CEMPLANG - ernawati, erna; Nirwana, Testa Pradia; Kusumadinata, Ali Alamsyah (JURNAL KAJIAN ISLAM MODERN, 2024)
Community is a form of solidarity in society. The solidity of the organization born in society can be formed from hobbies, work, and pleasure. The purpose of this study was to determine group communication activities carried out at BSC which is a Vespa community. This research method uses a qualitative approach where the technical data collection uses interviews and observations. The results of this study showed that group communication was carried out horizontally and using the WhatsApp application. This activity is carried out every time there is a new issue or activity to be carried out, the message to each group will be packaged. In addition, the routine agenda in the activity is to discuss village youth activities and about machines. The BSC community provides social innovation opportunities for youth to enjoy productive activities in social gatherings. Keywords Scooters community, communication, group